Pallister-Hall Syndrome Presenting in Adolescence - Aria Mahtabfar; Niall Buckley; Susan Murphy; Shabbar Danish; Ian Marshall (Case Reports in Genetics)
Pallister-Hall syndrome (PHS) is an extremely rare syndrome of unknown prevalence with autosomal dominant inheritance due to GLI3 gene mutations classically characterized by the presence of a hypothalamic hamartoma and polydactyly. Additional diagnostic criteria include bifid epiglottis, imperforate anus, small nails, hypopituitarism, growth hormone deficiency, and genital hypoplasia. It is typically diagnosed in infancy and early childhood, presenting with seizures and/or precocious puberty due to the hypothalamic hamartoma, and with limb anomalies due to central polydactyly. Our patient had presented with polysyndactyly at birth. However, as this is not uncommon in infants and is usually as part of the sporadic, isolated form of polydactyly, no further work up was done. He then presented at age 16 years with a headache and subjective visual changes, with brain imaging revealing a hypothalamic hamartoma. He did not have a history of seizures or central precocious puberty. Genotyping revealed a pathogenic variant affecting the GLI3 gene. We encourage all clinicians to consider PHS or an associated syndrome with a clinical finding of polydactyly. Further, as the natural history continues to reveal itself, this patient’s presentation provides important new data to the broad phenotypic spectrum of PHS.